Average Characteristics of Low‐Latitude Interhemispheric and F Region Dynamo Currents Deduced From the Swarm Satellite Constellation. Issue 12 (21st December 2019) - Lühr, Hermann; Kervalishvili, Guram N.; Stolle, Claudia; Rauberg, Jan; Michaelis, Ingo
Abstract: Based on magnetic field data from the Swarm satellite constellation advanced estimates of field‐aligned and radial currents at middle and low latitudes can be derived. Detailed results have been obtained for low‐latitude (14°–35° magnetic latitude) interhemispheric field‐aligned currents related to the solar quiet ( Sq ) current system. The continuous data set of five years allows resolving the dependences on local time, season, and longitude. We confirm the known current flow from the southern to the northern hemisphere around June solstice. Unexpected results are obtained for the months following December. Stratospheric sudden warming events are suggested as a reason for that. These phenomena are known to amplify lunar tides and atmospheric planetary waves. Furthermore, we investigated the mean characteristic of the meridional current systems connected to the wind‐driven F region dynamo above the magnetic equator. Typical features of radially downward currents around noon and upward currents in the evening sector could be confirmed. From a detailed analysis of the connected field‐aligned current distribution we deduced that the mean altitude of the dynamo region is higher in the evening than around noon. And it appears also at greater heights in the western hemisphere than in the eastern. Special current configurations are encountered in the longitude range containing the South Atlantic Anomaly. Here summer‐like conditions are prevailing through all seasons. This infers that the ionospheric conductivity is significantly enhanced in this region of weak magnetic field strength. Key Points: Average characteristics of field‐aligned and radial currents at low and equatorial latitudes are derived from dual‐spacecraft approach Low‐latitude interhemispheric field‐aligned currents show unexpected results during northern winter months The F region dynamo region above the magnetic equator are found at altitudes depending on longitude, local time, and season